Pancreatic β-Cell Identity in Diabetes - Remedi, Maria S. (Diabetes Obes Metab, 2016)
Recovery of functional β-cell mass continues to be an ongoing challenge in treating diabetes. Initial work studying β-cells suggested apoptotic β-cell death as a main contributor for the loss of β-cell mass in diabetes. Restoration of β-cells either by transplant or stimulating proliferation of remaining β-cells or precursors would then logically be a viable therapeutic option for diabetes. However, recent work has highlighted the inherent β-cell plasticity and the critical role of loss of β-cell identity in diabetes, and has suggested that β-cells fail to maintain a fully differentiated glucose-responsive and drug-responsive state, particularly in diabetic individuals with poorly-controlled, long-lasting periods of hyperglycemia. Understanding the underlying mechanisms of loss of β-cell identity and conversion in other cell types, as well as how to regain their mature differentiated functional state, is critical to develop novel therapeutic strategies to prevent or reverse these processes. In this review, we discuss the role of plasticity and loss of β-cell identity in diabetes, the current understanding of mechanisms involved in altering this mature functional β-cell state, and potential progresses to identify novel therapeutic targets providing better opportunities for slowing or preventing diabetes progression.